Student Learning Outcome Assessment for an Information Organization Curriculum Based on the Kirkpatrick Framework - Wang, Mei-Ling; Chang, Ai-Chi (Qualitative and Quantitative Methods in Libraries; Vol 6 No 4 (2017): December 2017 Issue, 2019)
This study aimed to use the Kirkpartick four-stage model to evaluate the learning outcomes of information organization (IO) courses. The objectives of the study were as follows: (1) to evaluate the learning outcome of information organization courses using the Kirkpatrick model; (2) to apply cataloging core competencies to course design for information organization curricula; (3) to explore the learning process and learning outcome of graduate students on information organization courses. The study used the learning outcome evaluation method and case studies; the evaluation method was used to transform the expected achievement and course goal according to cataloging competency. The "information organization" (IO) and the students on the course at National Chengchi University during 2016 fall semester were selected as the case study. The study population consisted of 33 graduate students of two classes. Cataloging competencies were transformed into learning objectives and ten course units of 14 sessions for the IO course, including information organization concept, descriptive cataloging, subject analysis, authority control, cataloging management and technology. The study used the 4–stage Kirkpatrick model to evaluate the student learning outcome of the IO course, including evaluation level 1 reaction, level 2 learning, level 3 behavior and level 4 results. The empirical data collected from the course tasks was used to evaluate level 2 through three assignments, four tests, and final examination. A questionnaire survey was used to evaluate level 1, 3, 4. The results of student satisfaction score was 4.51, showing with the IO course. As the average student achievement score was 83.48 points, the post-test scores of two classes’ graduate students were significantly higher than the pre-test scores, the study thus proved that students learn effective results. In conclusion, the results demonstrated that students were more confident in their study and work, their behavior changed and positive learning results were gained after studying on the IO course. Based on the Kirkpatrick model, the results provide favorable evidence for course effectiveness and its value and the students learned well on the information organization course.